Cooperativism and blockchain - Mendoza Munar, Lainiver; Riascos Díaz, Andrés A. (Cooperativismo & Desarrollo, 2024)
This article shows how, through blockchain, it would be possible to make secure barter through atypical contracts between the parties, the contract would be with global scope and with relativization of the autonomy of the private will. Blockchain is a software technology that allows validation; this is very important since the confirmation of a piece of information can lead to a series of processes and modifications in commercial relationships. On the other hand, cooperativism in Colombia in its associative part is regulated mainly by Law 79 of 1988, which establishes its own regulations for the cooperative sector and by Law 454 of 1998 that defines its conceptual framework clearly focusing on economic activity oriented towards a social benefit that corresponds to what the Fenwick Pioneers in Scotland and the Rochdale Pioneers in England inspired. The analyzes made in this study allow us to glimpse how Blockchain allows establishing trust between agents who have conflicting interests. This work aims to make visible the possibilities of the use of blockchain technology, especially with the implementation of secure barter to achieve a new tool for the development of the cooperative sector, providing trust, transparency, and immutability to transactions.